Scaling climate resilience: local agro-climatic committees reach 7,795 Cambodian Farmers in the Lower Mekong Basin - Le, Tam Thi; Khieng, Phanna; Thy, Or; Swaans, Cornelis (2025)
Across four districts of Prey Veng and Takeo provinces in the Lower Mekong Basin (LMB) in Cambodia, a total of 7,795 smallholder rice farmers (71% women) from 24 agricultural cooperatives used seasonal agroclimatic advisories in their planning and decision-making to improve climate-risk management. The Local Technical Agroclimatic Committees (LTACs) develop agroclimatic advisories for different climate scenarios based on Crop Decision Trees (CDTs).